In vitro activity of dihydropyrazole derivatives against Candida species - Khadija Abdelrahmman; Mohammed F. El-Behairy; Muhammad A. Alsherbiny; Tarek E. Mazeed (Faculty of Pharmacy, Cairo University, 2018)
Profound insights for efficient antifungal agents are required for the increased hazardous fungal infections caused by yeast, such as Candida species. In this study, we investigate the efficacy of different benzodioxolpyrazoline derivatives against two Candida species. All compounds exhibited potent in vitro antifungal activity against both species. Compound 5 showed the best inhibition zone in comparison to positive controls for Candida albicans. For Candida parapsilosis, all the tested compounds were active while the positive controls were inactive. These compounds provide good starting models for the development of new antimicrobial agents which could be useful especially for the treatment of candidiasis.